From Scribal Error to Rewriting How Ancient Texts Could and Could Not Be Changed - Kharanauli, Anna; Roselli, Amneris; Trebolle, Julio; Troyer, Kristin De (De Septuaginta Investigationes (DSI), 2020)
How ancient texts could and could not be changed has been in the focus of vibrant scholarly discussions in recent years. The present volume offers contributions from a representative group of prominent scholars from different backgrounds and specialties in the areas of Classical and Biblical studies who were gathered at an interdisciplinary symposium held in May 2015 at the Ivane Javakhishvili Tbilisi State University in Tbilisi, Georgia. In the first part of the volume Ancient Scribal and Editorial Practices, the authors approach ancient scribal and editorial techniques in Greek, Latin, and Syriac sources concerning classical and biblical texts, their textual criticism, and editorial history. The second part Textual History of the Hebrew Bible focuses on scribal and editorial aspects of the textual history of the Hebrew Bible. The third part Writing and Rewriting in Translation deals with a variety of writings from the Old Testament, New Testament, Apocrypha, and Patristic texts in various languages (Greek, Coptic, Arabic, Armenian, and Georgian), focusing on issues of textual criticism and translation technique. The volume contains an especially rich assortment of contributions by Georgian textual scholars concerning ancient editorial practices and ancient Georgian translations of biblical and patristic texts. This collection of papers provides insights into a variety of different areas of study that seldom come into contact with each other but are clearly in many ways related